Jekleni silosi za sipke materiale - Petrovčič, Simon (Gradbeni vestnik, 2009)
In the paper, the expressions for membrane forces in an axisymmetric steel silo structure at filling and discharge with a particulate solid material are presented. Graphical plots of these expressions are given. They can be used for a quick and easy estimate of membrane forces distribution in all parts of a silo structure. The plots are valid for any silo geometry and for any material stored. The influence of silo geometry and stored material properties on the size and distribution of membrane forces can be thus checked. The paper completes with an illustrative example where actions (pressure loads) at filling and discharge on the walls of a silo are computed and the corresponding membrane forces are evaluated.
Keywords: obtežba; polnjenje; praznenje; silosi